Being Digital: Why Addressing Culture and Creating a Digital Mindset are Critical to Successful Transformation. Issue 1 (12th April 2022) - Forsythe, John; Rafoth, Jason
ABSTRACT: Technology continues to drive nearly every aspect of our daily lives – both personal and professional. As organizations race, and sometimes fail, to adopt digital change, we must continually ask ourselves what drives a successful digital transformation? We believe that true transformational change can only be achieved when technology & culture are in lockstep, creating the necessary Digital Mindset to not only deploy the correct solutions, but the right organizational culture is in place to adopt and accelerate the technical change. Being Digital is about more than the technology an organization deploys; it is about the very fabric of that organization's character — their Digital DNA. Only when we fully cultivate the right mindset can we set the conditions for the right culture to flourish and ascend from merely doing digital things to truly Being Digital.